2012
DOI: 10.1590/s0101-20612012005000083
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mode and Effect Analysis (FMEA) for confectionery manufacturing in developing countries: Turkish delight production as a case study

Abstract: The Failure Mode and Effect Analysis (FMEA) was applied for risk assessment of confectionary manufacturing, in whichthe traditional methods and equipment were intensively used in the production. Potential failure modes and effects as well as their possible causes were identified in the process flow. Processing stages that involve intensive handling of food by workers had the highest risk priority numbers (RPN = 216 and 189), followed by chemical contamination risks in different stages of the process. The appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Quick observations and actions to eliminate the cause of detected nonconformities during food preparation, as well as the adoption of preventive and corrective measures, are essential to ensure hygienic-sanitary conditions because any failure during any of the stages of preparation may jeopardize and harm the food that is being prepared (BADARÓ; AZEREDO; ALMEIDA, 2007;OZILGEN, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Quick observations and actions to eliminate the cause of detected nonconformities during food preparation, as well as the adoption of preventive and corrective measures, are essential to ensure hygienic-sanitary conditions because any failure during any of the stages of preparation may jeopardize and harm the food that is being prepared (BADARÓ; AZEREDO; ALMEIDA, 2007;OZILGEN, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Special clothing, hats and gloves were not effectively used on the process lines (especially in confectionary B). We chose sampling points in our study according to observations and information in the literature (Batu & Kırmacı, 2006;_ Ipek & Zorba, 2007;G€ ok & Batu, 2008;€ Ozilgen, 2012). Batu & Kırmacı (2006) reported that the main problem points for lokum production lines were raw materials, cooking method, personnel, plant hygiene, packaging and storage.…”
Section: Discussionmentioning
confidence: 99%
“…The remedial actions can be developed through the factor analysis [4]. Practicing the logical mechanism of managing the risk has lowered the value of RPN below 100 which is the limit of acceptance [5]. Improvement as a continuous progress through the measures on operation procedure standardization, inspection throughout the process are established through FMEA [6].…”
Section: Literature Reviewmentioning
confidence: 99%